Removal of Arsenic from Groundwater Utilizing a Semicircular Section Tubular Photo-Reactor in Continuous Mode Operation - Escalera, Ramiro; Ormachea, Omar (Current Approaches in Science and Technology Research Vol. 14, 2021)
A practical low-cost treatment system of suitable capacity was developed in order to satisfy drinking water consumption needs of people living in small rural villages affected by arsenic contamination. The system is based on a semicircular section tubular photo-reactor which has been constructed, characterized and applied to the treatment of groundwater contaminated with As (V) by means of the solar oxidation and removal of arsenic (SORAS) technique, using ferrous and citrate salts. The solar concentrator was made from recyclable waste materials such as fluorescent lamp glass tubes and 6” PVC pipes cut in half and covered in aluminium foil. Solar radiation is concentrated to 2.8 times its natural intensity in the reactor. When compared to a fluorescent light glass tube alone and a 2-liter PET bottle, batch irradiation trials followed by controlled agitation (shear rate = 30 – 33 s-1; 20 min agitation period) revealed that the photo-reactor promotes the development of settleable floccules (Dp > 0.5 mm). c In the photo-reactor, the fluorescent lamp tube, and the PET bottle, the required irradiation times for floccule generation were 15, 25, and 60 minutes, respectively. Continuous flow investigations utilising a photo-reactor with a photo-collection area of 0.9 m2 and a hydraulic retention duration (equivalent to the irradiation period) of 15 minutes revealed that when the solution is agitated moderately, good settleability floccules form immediately (33 s-1). With a final concentration of 16.5 mg/L in decanted water, an As (V) removal efficiency of 98.36 percent was achieved. According to these findings, at UVA irradiation intensities of 50-70 W/m2, the photo-reactor can treat roughly 130 L/m2 in a 5-hour period. This daily capacity can supply safe water to a 4 - person family at a consumption rate of 30-35 L/person/day, a typical value in rural areas in the Bolivian Altiplano.